Przemiany społeczno-kulturalne wsi Sudzin i Sudzinek na przestrzeni XX i początku XXI wieku - Kopera, Łukasz (Zeszyty Wiejskie, 2012)
This article is the first attempt to depict the socio-cultural aspects of the villages Sudzin and Sudzinek in the twentieth and twenty-first century. These villages are located in the south-eastern boarder of the Łódź region (Żytno community) and they used to be owned by the Ostrowskich family estate, and then Potockich’s from Mulszyn. The view of villages, over seventy / eighty years ago, show us the oldest citizens, who are now eighty or even ninety years old. Among them there are people who were born here, who went “into the world” or who are still living here, and also those who came to these villages, for example by marriage. The article is an interesting contribution to the issues of regionalism, which consists of community matters, buildings, infrastructure, traditions, and sources of income. Issues such as beliefs and rituals have been widely considered in the Radomszczański county and the region of Łódź.